The significance of internal calcifications on perinatal post-mortem radiographs. Issue 7 (July 2020) - Reid, C.; Arthurs, O.J.; Calder, A.D.; Sebire, N.J.; Shelmerdine, S.C.
Abstract : AIM: To determine whether the presence of internal calcifications on perinatal post-mortem skeletal surveys (PMSS) are associated with certain diagnoses of fetal loss. METHODS AND MATERIALS: A 6-month retrospective, single-centre, cohort study was conducted on PMSS performed for perinatal death assessment. One reader re-reviewed all PMSS images for the presence and location of internal calcifications, and noted whether these were included within the original radiology report. Findings at autopsy were then reviewed independently by a second researcher and cause of fetal loss or main diagnosis recorded. Chi-squared tests were conducted to identify differences between those with and without internal calcifications at PMSS. RESULTS: Two hundred and thirty perinatal deaths (mean gestational age 18 weeks; average 12–35 weeks) were included in the study, of which 42 (18.3%) demonstrated intra-abdominal calcifications, and 16/42 (38.1%) were mentioned in the radiology reports. Most calcifications were found to be within the lumen of the gastrointestinal tract, and in the left upper quadrant of the abdomen. There was no statistical difference between identifiable causes for fetal loss at autopsy in cases with and without calcification at PMSS (59.5% versus 58.5% respectively, p =0.904). Nevertheless, where calcification and a cause for fetal loss were found, the aetiology was more likely to be due a fetal rather than placental issue. CONCLUSION: The presence of internal calcifications on PMSS was not associated with an increased likelihood of explainable fetal loss or particular diagnosis at autopsy. Highlights: Fetal calcifications on post-mortem skeletal surveys are not significantly associated with causes of fetal loss. When present, internal calcifications were usually seen in lower gestational aged fetuses, intra-abdominal in location, with the majority being intraluminal. The majority of radiologists do not report internal fetal calcifications on radiographs, without significant consequences for final outcome at autopsy.